Visionary Leadership Strategies for Sustaining Madrasah Culture in Industry 4.0 - Syam, Aldo Redho; Supadi, Supadi; Mayasari, Linda Ika; Takdir, Muh.; Noh, Mohd Aderi Che (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – The purpose of this study is to explore visionary leadership strategies for sustaining and developing madrasah culture at the secondary school level (e.g., MTs and MA) in the industry 4.0 era. It examines how effective leadership can preserve traditional values while adapting to technological advancements in education.Method – A literature review approach was employed, analyzing data from databases such as Google Scholar, JSTOR, and Scopus (2010-2025). Keywords included